Practical research - Leedy, Paul D.; Ormrod, Jeanne Ellis (Upper Saddle River, N.J. : Merrill Prentice Hall, 2001)
This book is divided into five parts: The Fundamentals; Focusing Your Research Efforts; Qualitative Research Methodologies; Quantitative Research Methodologies; and Preparing the Research Report.
Keywords: Research; Methodology; Research -- Methodology